Bridging the virtual and hands-on laboratories for small-signal amplifier circuits - Abd Halim, Wahidah; Subanthiran, Dinesh; Ahmad Tarusan, Siti Azura; Jidin, Auzani; Mat Rosdi, Muhammad Zaim; Mohd Ali, Muhammad Rabani (2024)
This paper presents an innovative approach to teach bipolar junction transistor (BJT) small-signal amplifier circuits in the laboratory, with a focus on simplifying the learning process for undergraduate students. In traditional Analog Electronics laboratory, students often face difficulties in constructing analog electronics circuits on breadboard, sometimes struggling even to begin the experiment. While BJT small-signal amplifiers may appear to be a basic analog electronics application, they remain one of the more challenging circuits for students to successfully assemble during lab sessions. To further enrich the educational experience, a multifaceted instructional approach is proposed. Tinkercad was utilized as an educational tool, effectively bridging the gap between theoretical concepts and practical application to enhance understanding of BJT small-signal amplifier configurations. Furthermore, EasyEDA was used to design a custom printed circuit board (PCB) for integration of BJT small-signal amplifier configurations onto an educational trainer board. These configurations comprised common-emitter, common-collector, and common-base amplifiers. This trainer board aims to streamline the hands-on experience, enrich students’ knowledge and competencies, and reduce the learning time taken to understand the small-signal amplifier circuit concept.